Sepasar As A Hybrid Educational Media And OnlineMarketing Of Sambilegi Market Traders In Covid-19 Pandemic - Awan Santosa; Sri Handayani; Pande Nyoman Ariyuda; Mohd Fadhil Harfiez Abdul Muttalib (International Journal Of Community Service, 2023)
The important function of traditional markets is not only as a market for selling local (local) community products, but also as employment opportunities that are very beneficial for the community. One of the traditional markets located in Slemn Regency is Sambilegi Market. Sambilegi Market is one of the driving forces in driving economic growth and mobilizing the community. The conditions in the Sambilegi market are the weak organizational network of traders which results in weak unity and inter-market networks . Therefore, technology must be treated specifically if businesses are to survive and thrive. Digital technologies create new economic dynamics and social environments that need to be managed for technological changes in industry and society to provide long-term and far-reaching benefits. Opportunities and opportunities for Sepasar.id to apply institutional engineering models and support the transformation of traditional markets in the digital era. The traditional market digitization model embodies several institutional elements, such as organizational, human resources, business, and network elements. In addition, training is given to volunteers who will go directly to the market to assist traders in learning the video material that has been prepared. The expected output target of the joint community empowerment program Sepasar.id is exists enhancement knowledge, skills, HR capacity and organization, as well as digital literacy of Sambilegi market traders.